Design of an AI-driven home-based pulmonary telerehabilitation system to enhance patient engagement - Chien, Shih-Ying; Hu, Han-Chung; Tseng, Winston (Digital health, 2025)
Pulmonary telerehabilitation (PTR) has emerged as a promising mobile health approach to address post-discharge challenges faced by patients with chronic pulmonary disease (CPD), including limited professional support, physical discomfort, and declining motivation that may compromise adherence and lung function. Challenges exist in traditional hospital-based rehabilitation, constrained by logistics, limited capacity, and accessibility, especially for elderly or mobility-impaired individuals. This study aimed to investigate the feasibility and usability of a novel home-based PTR system (Intelligent Pulmonary Rehabilitation Exercise System (IPRES)), eliciting user experience reported by a cohort of outpatients with relevant respiratory diseases. This questionnaire-based, quantitative, single-group pretest-posttest pilot study involved 36 post-discharge CPD patients, predominantly at GOLD stage 3, transitioning from hospital-based to home-based pulmonary rehabilitation Participants completed structured IPRES exercise sessions, including recumbent cycling with gamified modules and real-time physiological monitoring. Usability was assessed using the System Usability Scale (SUS) and complementary questionnaires on engagement, motivation, and behavioral intention, providing insights into technical usability and patient-centered facilitators and barriers. Participants reported high usability, with a mean SUS score of 78.87 ± 6.32. Qualitative feedback indicated that personalized feedback, collaborative goal-setting, and gamified interactions enhanced engagement and motivation, with participants highlighting improved understanding of exercise goals, increased confidence in self-managing rehabilitation, and enjoyment of interactive training tasks. This pilot study demonstrates that IPRES is feasible and well-received, highlighting usability strengths and engagement factors that can inform future optimization and randomized controlled trials. While medium- and long-term effectiveness requires further evaluation, these findings support the potential of IPRES as a scalable, patient-centered tool for home-based pulmonary rehabilitation.